Evaluating the Utility of a Structured Clinical Protocol for Reducing the Impact of Behavioural and Psychological Symptoms of Dementia in Progressive Neurological Diseases: A Pilot Study. (26th March 2018) - Ryan, Nicholas P.; Scott, Laura; McPhee, Maryanne; Mathers, Susan; Davis, Marie-Claire; Maule, Roxanne; Fisher, Fiona
Abstract : Objectives . Behavioural and psychological symptoms of dementia (BPSD) cause significant distress to both aged care residents and staff. Despite the high prevalence of BPSD in progressive neurological diseases (PNDs) such as multiple sclerosis, Huntington's disease, and Parkinson's disease, the utility of a structured clinical protocol for reducing BPSD has not been systematically evaluated in PND populations. Method . Staff (n = 51 ) and individuals with a diagnosis of PND (n = 13 ) were recruited into the study, which aimed to evaluate the efficacy of a PND-specific structured clinical protocol for reducing the impact of BPSD in residential aged care (RAC) and specialist disability accommodation (SDA) facilities. Staff were trained in the clinical protocol through face-to-face workshops, which were followed by 9 weeks of intensive clinical supervision to a subset of staff ("behaviour champions"). Staff and resident outcome measures were administered preintervention and immediately following the intervention. The primary outcome was frequency and severity of BPSD, measured using the Neuropsychiatric Inventory-Nursing Home Version (NPI-NH). The secondary outcome was staff coping assessed using the Strain in Dementia Care Scale (SDCS). Results . In SDA, significant reductions in staff ratings of job-related stress were observed alongside a statistically significant decrease in BPSD from T1 to T2. In RAC, there was no significant time effect for BPSD or staff coping; however, a medium effect size was observed for staff job stress. Conclusions . Staff training and clinical support in the use of a structured clinical protocol for managing BPSD were linked to reductions in staff job stress, which may in turn increase staff capacity to identify indicators of resident distress and respond accordingly. Site variation in outcomes may relate to organisational and workforce-level barriers that may be unique to the RAC context and should be systematically addressed in future RCT studies of larger PND samples.